2016
DOI: 10.1016/j.celrep.2016.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular Mast Cells Govern Shear Stress-Induced Arteriogenesis by Orchestrating Leukocyte Function

Abstract: The body has the capacity to compensate for an occluded artery by creating a natural bypass upon increased fluid shear stress. How this mechanical force is translated into collateral artery growth (arteriogenesis) is unresolved. We show that extravasation of neutrophils mediated by the platelet receptor GPIbα and uPA results in Nox2-derived reactive oxygen radicals, which activate perivascular mast cells. These c-kit(+)/CXCR-4(+) cells stimulate arteriogenesis by recruiting additional neutrophils as well as gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(100 citation statements)
references
References 44 publications
6
84
1
Order By: Relevance
“…Therefore, large vascular smooth muscle containing vessels are not required for recruitment, differentiation, and/or retention of mast cells in critical bone defects as we previously proposed . Moreover, these finding suggest that mast cells may be a source of the vascular endothelial growth factors and angiopoietin‐2 that drives angiogenesis and subsequent arteriogenesis, as has been reported in other models . Thus, formally testing this, and elucidating the mechanisms responsible for mast cell accumulation in critical defects remain important areas for future investigation.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Therefore, large vascular smooth muscle containing vessels are not required for recruitment, differentiation, and/or retention of mast cells in critical bone defects as we previously proposed . Moreover, these finding suggest that mast cells may be a source of the vascular endothelial growth factors and angiopoietin‐2 that drives angiogenesis and subsequent arteriogenesis, as has been reported in other models . Thus, formally testing this, and elucidating the mechanisms responsible for mast cell accumulation in critical defects remain important areas for future investigation.…”
Section: Discussionsupporting
confidence: 63%
“…In contrast, perivascular mast cells play a central role in regulating shear stress–induced arteriogenesis by orchestrating leukocyte function and growth factor/cytokine release. This leads to a vicious cycle of mast cell recruitment and activation, and stimulation of arteriogenesis via recruitment of neutrophils, monocytes, and T cells …”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies showed that MCs play a regulatory role in arteriogenesis, the process of shear stress‐induced growth of collateral vessels (11). Following the induction of arteriogenesis by FAL in mice for 24 h, immunohisto‐chemical analysis of adductor muscle tissue revealed the presence of c‐kit‐, tryptase‐, and rRNA‐positive MCs around growing collaterals.…”
Section: Resultsmentioning
confidence: 99%
“…Using the murine hind limb model of arteriogenesis, following FAL, the subsequent reperfusion was significantly increased in mice that underwent procedures to activate MCs in vivo , particularly using degranulating agents such as compound 48/80. Furthermore, under these circumstances, mobilized and degranulated MCs were located in close proximity to growing collateral vessels, as compared with sham‐operated controls (11). Our follow‐up study now demonstrates that rRNA‐containing MCs and free eRNA were located in close proximity to growing collateral arteries.…”
Section: Discussionmentioning
confidence: 98%
“…Similar to macrophages, mast cells originate in the bone marrow from the common myeloid progenitor, migrate to the vasculature as a mast cell progenitor, and fully mature in tissues, where their functional phenotype is plastic and determined by the microenvironment. Mature mast cells are often situated perivascularly and can have profound effects on vascular tone, edema, and angiogenesis . When angiogenesis occurs during remodeling, it is preceded or accompanied by macrophage and neutrophil influx that has been argued to be mast cell‐mediated .…”
Section: Introductionmentioning
confidence: 99%